Measuring latent listening strategies: Development and validation of the EFL listening strategy inventory. (April 2016) - Nix, John-Michael L.
Abstract: The present research identified the structure of latent trait listening strategy use by developing and validating an inventory of EFL listening strategic knowledge. Results of factor analysis and multi-dimensional item response theory (MIRT) analysis utilizing responses from 315 subjects identified and confirmed a two-dimensional structure composed of top–down and bottom–up processing strategy types. These constructs are shown to have robust correlations with listening comprehension and also exhibit robust inter-correlation, providing empirical support for the formal model of interactive processing. It was revealed that bottom–up strategies do not exert direct effects on listening comprehension, but must be mediated by top–down strategies. Results are discussed in light of extant strategy effect studies. Future research to test the generalizability of the inventory across cultural contexts and to gauge its feasibility in pedagogical applications is suggested.